Odpowiedzi

2009-12-17T20:07:37+01:00
∫4a - 2 =b
∫3a + 7b = 1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
31a=1,5+14

b=4a-2
31a=15,5 /:31

b=4a-2
a=0,5

b=4*0,5-2
a=0,5

b=2-2
a=0,5

b=0
a=0,5
2009-12-17T20:10:45+01:00
∫4a - 2 =b
∫3a + 7b = 1,5

4a + b = 2 // x(-3)
3a + 7b = 1,5 // x4

-12a - 3b = -6
12a + 28 b = 6

25b = 0 // : 25
b = 0

b= 0
3a + 7x0 = 1,5

b=0
3a + 0 = 1,5

b=0
3a=1,5 // :3

b= 0
a= 0,5

Proszę i życzę samych piątek ;)
  • Użytkownik Zadane
2009-12-17T20:10:56+01:00
∫4a - 2 =b
∫3a + 7b = 1,5

∫b=4a - 2
∫3a + 7 *(4a - 2) = 1.5

∫b= 4a - 2
∫3a + 28a - 14 = 1.5

∫b= 4a - 2
∫31a = 14 + 1.5

∫b=4a - 2
∫31a = 15.5/31

∫ b= 4a - 2
∫a = 0.5

∫a = 0.5
∫b= 4 * 0.5 - 2

∫a- 0,5
∫b= 0